Cryoprotective ability of starch syrup in the composition of aromatic and fruit-berry ice cream - Polishchuk, Galyna; Bass, Oksana; Osmak (Fedchenko), Tetiana; Breus, Natalia (My University, 2019)
For complete replacement of sugar in the ice cream the starch syrup of different degree of saccharinization was chosen: glucose-fructose syrup GFS (dextrose equivalent 98) and syrup caramel SC (dextrose equivalent 30). GFS, in comparison with control samples with sugar, due to the high content of mono-sugars, significantly reduces the cryoscopic temperature of the mixtures. While, the SC boosts this figure. Therefore, in order to maintain the recommended balance on the content of frozen water at each stage of low-temperature processing of ice cream mixtures, it is expedient to combine the cryoprotective capacity of the syrup with different dextrose equivalent. The ranges of optimal correlations between GFS and SC in compositions were calculated, allowing to receive the content of frozen water, according to control samples – from 30:70 to 40:60 for aromatic ice cream and from 50:50 to 90:10 – for fruit-berry ice-cream. Microstructural analysis of ice cream samples has demonstrated the expediency of complete replacement of sugar on the syrup compositions, which provides the formation of a more homogeneous finished product structure, compared with control samples with sugar.Для повної заміни цукру в морозиві було обрано крохмальний сироп різного ступеня сахаринізації: глюкозо-фруктозний сироп GFS (декстрозний еквівалент 98) та сироп карамельний SC (декстрозний еквівалент 30). GFS, порівняно з контрольними зразками з цукром, завдяки високому вмісту моно-цукрів значно знижує кріоскопічну температуру сумішей. У той час як НС збільшує цю цифру. Тому, щоб підтримувати рекомендований баланс за вмістом замерзлої води на кожному етапі низькотемпературної обробки сумішей з морозивом, доцільно поєднувати кріопротекторну здатність сиропу з різним еквівалентом декстрози. Діапазони оптимальних співвідношень між GFS та SC у композиціях розраховувались, що дозволяло отримувати вміст замороженої води, за контрольними зразками - від 30:70 до 40:60 для ароматичного морозива та від 50:50 до 90:10 - для фруктово-ягідного морозива. Мікроструктурний аналіз зразків морозива продемонстрував доцільність повної заміни цукру на сиропних композиціях, що забезпечує формування більш однорідної структури готового продукту порівняно з контрольними зразками з цукром.
Keywords: морозиво; кріоскопічна температура; оптимізація складу; ice cream; cryoscopic temperature; composition optimization; кафедра технології молока і молочних продуктів; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки